Interactive educational tool for the design of compensators using frequency response analysis. Issue 1 (January 2018) - Yadav, Drishti; Patel, RN
This article provides a didactic platform that is developed to improve the teaching as well as learning of "design of compensators" in control systems engineering. The educational tool comprises a graphical user interface in MATLAB. The graphical user interface permits an individual to investigate various parameters involved in the design of the required compensator, which includes percentage overshoot, peak time, and velocity error constant and observe the results dynamically as the parameters change. The approach used in this article for the design of compensators is based on the frequency response analysis. One can obtain various plots including unit step response plot, Bode plot, and root locus plot for uncompensated and compensated systems to have a better understanding of the designed compensator.